(untitled) (Polish Yearbook of International Law, 2017)
This article investigates the engagement of EU law with the interests represented and pursued by the Member States within the framework of the European Union. In principle, because the interests which the Member States feed into the EU governance machinery are formulated in political processes at the national level, and thus possess paramount political legitimacy, EU law may only interact with those interests when a clear and sufcient mandate has been provided for doing so. Such mandates follow from Treaty provisions or EU legislation. They embody common political agreements among the Member States by which they commit themselves to realising the specifc interests they share, as well as achieving related common policy objectives. In practice, however, the boundaries of EU law’s mandate are difficult to determine with precision, and this may weaken the legitimacy of EU law’s interventions. The weaker legitimacy of the law raises particular problems in the law of the Single Market, where the interests pursued by national governments are subjected to filtering, moderation, and even transformation by the Court of Justice.